2023
DOI: 10.1177/11795514221145841
|View full text |Cite
|
Sign up to set email alerts
|

Stress Induced Cortisol Release Depresses The Secretion of Testosterone in Patients With Type 2 Diabetes Mellitus

Abstract: Background: Both hormonal and genetic data reveal that the stress hormone cortisol and its regulating genes may affect the level of testosterone in humans. It is uncertain whether type 2 diabetes mellitus would manifest similarly. Furthermore, a genetic strategy to screen out the stress system genes that may contribute to testosterone decline in humans is less understood. Objectives: In this study, we aimed to elucidate the link between stress and testosterone levels, both hormonally and genetically. Method: T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…An important aspect of corticosteroids is their regulation of blood vessel reactivity, affecting blood flow and pressure [203,216], largely in contraposition to DHEA (dehydroepiandrosterone) [217,218]; interacting with T (and other androgens), E2 [110,188,219], and insulin [220,221]; and even acting in coordination with catecholamines [222,223]. Corticosteroids also show a critical effect on behavior, in conjunction with other steroid hormones [224,225], including appetite (via a myriad of additional cytokines, non-coding RNAs, and other protein factors). The relationship with neural transmission and the modulation of the complex nature of depression has been also acknowledged, but the mechanisms have not yet been fully established [226][227][228].…”
Section: Ms Main Paths and Mechanismsmentioning
confidence: 99%
“…An important aspect of corticosteroids is their regulation of blood vessel reactivity, affecting blood flow and pressure [203,216], largely in contraposition to DHEA (dehydroepiandrosterone) [217,218]; interacting with T (and other androgens), E2 [110,188,219], and insulin [220,221]; and even acting in coordination with catecholamines [222,223]. Corticosteroids also show a critical effect on behavior, in conjunction with other steroid hormones [224,225], including appetite (via a myriad of additional cytokines, non-coding RNAs, and other protein factors). The relationship with neural transmission and the modulation of the complex nature of depression has been also acknowledged, but the mechanisms have not yet been fully established [226][227][228].…”
Section: Ms Main Paths and Mechanismsmentioning
confidence: 99%
“…Additionally, research has highlighted the role of stress-related hormones, such as cortisol, in modulating the physiology of the androgen system. Elevated cortisol levels, commonly observed during stress, have been associated with reduced testosterone levels and altered androgen signaling pathways [ 106 , 107 ]. However, a study found that testosterone levels increased after acute stress exposure in all groups, regardless of borderline personality disorder (BPD) or posttraumatic stress disorder (PTSD) status, suggesting that stress-related changes in testosterone release are not influenced by these disorders in young adult men [ 108 ].…”
Section: Introductionmentioning
confidence: 99%